Desempenho De Um Sistema De Irrigação Por Gotejamento Utilizando Energia Fotovoltaica - Zago, Emmanuelle Albara (2017)
The focus of this project was the use of a water pumping system for drip irrigation. The energy for such pumping was obtained by means of a small-sized photovoltaic panel of Greatwatt's horizontal axis installed on a self-supporting tower and a water pump of the brand SHURflo model 8000, it was installed in the project CASA (Analysis Center Of Alternative Systems). The trials were performed on sunny days, and cloudy and with few clouds, at different times and duplicates at each time. The energy produced was collected directly at the site and the irrigation capacity was obtained by collecting the water and its uniformity estimated by means of the Christiansen Uniformity Coefficient (CUC) and the Uniform Distribution Coefficient (CUD); The yield of the system varied according to the characteristics of the tests. The open sky days presented the highest values in relation to the energy produced, with an average of up to 15.1 Wh. On the other hand, the values of CUC and CUD were within acceptable range, most of them considered excellent or greater than 90%. In this way, it is possible to verify the feasibility of the use of a photovoltaic solar system to obtain energy for irrigation in small properties in the municipality of Cascavel-PR.